NADPH oxidase activity in pollen tubes is affected by calcium ions, signaling phospholipids and Rac/Rop GTPases - Potocký, Martin; Pejchar, Přemysl; Gutkowska, Małgorzata; Jiménez-Quesada, María José; Potocká, Andrea; Alché, Juan de Dios; Kost, Benedikt; Žárský, Viktor (Journal of plant physiology, 2012)
Reactive oxygen species (ROS) generated by NADPH oxidase (NOX) are crucial for tip growth of pollen tubes. However, the regulation of NOX activity in pollen tubes remains unknown. Using purified plasma membrane fractions from tobacco and olive pollen and tobacco BY-2 cells, we demonstrate that pollen NOX is activated by calcium ions and low abundant signaling phospholipids, such as phosphatidic acid and phosphatidylinositol 4,5-bisphosphate in vitro and in vivo. Our data also suggest possible synergism between Ca(2+) and phospholipid-mediated NOX activation in pollen. Rac/Rop small GTPases are also necessary for normal pollen tube growth and have been proposed to regulate ROS production in root hairs. We show here elevated ROS formation in pollen tubes overexpressing wild-type NtRac5 and constitutively active NtRac5, while overexpression of dominant-negative NtRac5 led to a decrease of ROS in pollen tubes. We also show that PA formed by distinct phospholipases D (PLD) is involved in pathways both upstream and downstream of NOX-mediated ROS generation and identify NtPLDδ as a PLD isoform acting in the ROS response pathway.
Keywords: Hydrogen Peroxide; pylová láčka; Plant Proteins; monomerní proteiny vázající GTP; Nicotiana; peroxid vodíku; fosfolipidy; rac proteiny vázající GTP; Reactive Oxygen Species; signální transdukce; rac GTP-Binding Proteins; vápník; Signal Transduction; rostlinné proteiny; NADPH-oxidasy; Pollen Tube; Calcium; Phospholipids; Protein Isoforms; reaktivní formy kyslíku; NADPH Oxidases; exprese genu; Olea; protein - isoformy; buněčná membrána; tabák; Gene Expression; Cell Membrane; Monomeric GTP-Binding Proteins